ARDL Modeling of the Impact of Financial Reforms on Private Domestic Saving in Cameroon (Global Journal of Human-Social Science, 2019)
The aim of this study is to model the effects of financial sector reforms on private domestic savings in Cameroon After building an econometric model of private domestic savings from the theory of financial repression of McKinnon and Shaw 1973 it is analyzed using ARDL co integration approach The results indicate that there exist a long run negative and significant relationship between private domestic savings and financial reforms
Keywords: financial reforms; private domestic savings; ARDL modeling approach